2018
DOI: 10.3390/ijerph16010025
|View full text |Cite
|
Sign up to set email alerts
|

Four Wellbeing Patterns and their Antecedents in Millennials at Work

Abstract: Literature suggests that job satisfaction and health are related to each other in a synergic way. However, this might not always be the case, and they may present misaligned relationships. Considering job satisfaction and mental health as indicators of wellbeing at work, we aim to identify four patterns (i.e., satisfied-healthy, unsatisfied-unhealthy, satisfied-unhealthy, and unsatisfied-healthy) and some of their antecedents. In a sample of 783 young Spanish employees, a two-step cluster analysis procedure sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…For example, Toyama and Mauno (2016) found that the highest overall scores on the emotional intelligence dimensions trait were associated with higher well-being and job performance profiles, while the group with lower emotional intelligence showed negative outcomes. Likewise, Ayala et al (2017) found that overqualification characterizes the unhappy-productive pattern, and Abdi et al (2019) showed that higher levels of job importance and lower levels of role ambiguity mainly differentiate the satisfied-healthy pattern. Abdi et al (2019) also found that overqualification and role overload differentiate the unsatisfied-healthy and satisfied-unhealthy patterns, and role conflict also characterizes the satisfied-unhealthy pattern.…”
Section: Review Of the Patterns Of The Relationships Reported In The mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Toyama and Mauno (2016) found that the highest overall scores on the emotional intelligence dimensions trait were associated with higher well-being and job performance profiles, while the group with lower emotional intelligence showed negative outcomes. Likewise, Ayala et al (2017) found that overqualification characterizes the unhappy-productive pattern, and Abdi et al (2019) showed that higher levels of job importance and lower levels of role ambiguity mainly differentiate the satisfied-healthy pattern. Abdi et al (2019) also found that overqualification and role overload differentiate the unsatisfied-healthy and satisfied-unhealthy patterns, and role conflict also characterizes the satisfied-unhealthy pattern.…”
Section: Review Of the Patterns Of The Relationships Reported In The mentioning
confidence: 98%
“…Likewise, Ayala et al (2017) found that overqualification characterizes the unhappy-productive pattern, and Abdi et al (2019) showed that higher levels of job importance and lower levels of role ambiguity mainly differentiate the satisfied-healthy pattern. Abdi et al (2019) also found that overqualification and role overload differentiate the unsatisfied-healthy and satisfied-unhealthy patterns, and role conflict also characterizes the satisfied-unhealthy pattern.…”
Section: Review Of the Patterns Of The Relationships Reported In The mentioning
confidence: 98%
“…Some studies find that work overload is a characteristic of job satisfaction, despite leading to unhealthy patterns [8] mediated in turn by a desire for incentives, security status and the ability to be promoted [10,11]. Nonetheless, extensive literature shows that work overload is negatively related to health indicators [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Integrating the social identity theory, it could be argued that millennials’ (Generation-Y) group prestige and identification influence their organizational identification over a period of time, mediated by the perception of organizational identification. This embeddedness could help them mitigate stress, as their institutional socialization is evinced to help them exhibit prosocial and organizational behaviors (Abdi et al , 2019; Gorgenyi-Hegyes et al , 2021).…”
Section: Research Background and Related Literaturementioning
confidence: 99%